2019
DOI: 10.3390/pathogens8040248
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Molecular Identification of Brucella spp. in Pigs from Cairo and Giza Governorates, Egypt

Abstract: Brucellosis is considered as endemic disease of animals and humans since thousands of years in Egypt. However, brucellosis in pigs has never been reported in Egypt. Thus, serological and molecular assays were applied to detect anti-Brucella antibodies and DNA in serum samples collected from pigs. In total 331 blood samples collected from male and female pigs at slaughterhouses of Cairo and Giza governorates were investigated using Brucella c- and i-ELISA and Brucella real-time PCR. Anti-Brucella antibodies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…are known to have host preference, cross-infection has previously been reported to be common in areas where mixed husbandry systems are practised (11,28,29). Similarly, the presence of B. melitensis in pigs' serum was recently reported in Egypt (15), whose prevalence is also comparable to a previous report from Latin America where B. melitensis was detected in pigs (30). In this study, the positive pigs were sourced from peri-urban and slum areas, where small-scale farmers keep mixed herds that facilitates close contact between the different animal species.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…are known to have host preference, cross-infection has previously been reported to be common in areas where mixed husbandry systems are practised (11,28,29). Similarly, the presence of B. melitensis in pigs' serum was recently reported in Egypt (15), whose prevalence is also comparable to a previous report from Latin America where B. melitensis was detected in pigs (30). In this study, the positive pigs were sourced from peri-urban and slum areas, where small-scale farmers keep mixed herds that facilitates close contact between the different animal species.…”
Section: Discussionmentioning
confidence: 90%
“…in pig serum in East Africa. Brucellosis is a widespread zoonotic disease and serological evidence of pig brucellosis has previously been described in Africa (15,(22)(23)(24)(25)(26). South America and Southeast Asia are considered to have a higher prevalence of porcine brucellosis, as compared to the other regions including Africa (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in pig serum in East Africa. Brucellosis is a widespread zoonotic disease and serological evidence of pig brucellosis has previously been described in Africa (15,(18)(19)(20)(21)(22). However, information on B. spp.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that there is indeed a complex and diverse distribution of the pathogen among different hosts, further complicated by farming systems and close interactions between wildlife and livestock (12). Quantitative, real-time PCR assays, such as those developed by Matero et al (13) and Probert et al (14), have also significantly increased the ease of detection of Brucella DNA, moreover, with the extraction of genomic material directly from clinical specimens (15). These test options and findings have shed light on the complicated epidemiology and transmission of brucellosis between different hosts which, unfortunately, have not been applied to the pig population in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%